Inhibitory Power Solution Against Bacteria Leaf Beluntas Staphylococcus Aureus - Irmanita Wiradona; Erni Mardiati; Sulur Joyo Sukendro (Jurnal Riset Kesehatan, 2014)
The purpose of the study is to determine the effectiveness of the inhibition of leaf beluntas concentration of 5 % , 10 % , and 20 % against Staphylococcus aureus . With Staphylococcus aureus as the subjects, this quasi experimental study was conducted using 4 cup petri divided into 4 sections, then these were incubated for 24 hours. The data were analyzed descriptively and presented in a graphical form to see the difference in inhibition zone diameter of each concentration using One Way Anova test. The results shows a concentration of 5 % and 10 % with mean difference : 0.92 and p value = 0.003 means that there is a significant difference in this. Concentration differences of 5 % and 20 % of 3.2 with p value = 0.199, means that there is a significant difference between the inhibitory concentration. Concentration differences of 10 % and 20 % average of 0.6 means that there is a significant difference between the inhibitory concentrations. In conclusion, leaf beluntas solution are effective to inhibit the growth of staphylococcus aureus.